Богородиця в сучасних польських дослідженнях - Кметь, І. (Народна творчість та етнографія, 2008)
The article covers the most important issues of the modern investigation of Virgin Mary in Poland, notably: the Blessed Virgin in the church tradition; the Blessed Virgin is a guardian of Polish people, the image of the Blessed Virgin in folk Christianity. The investigation allows realizing the depth and modernity of the Virgin Mary theme in Polish and Ukrainian historiography.